L-lysine escinat, thiotriazolin, gordox and mydocalm influence on oxygen tension in the intestinal wall and acid-base balance and limited proteolysis in intestinal venous blood in terms of intraabdominal hypertension modeling. - Sapegin, V. I.; Sapegin, I. D.; Ilchenko, F. N. (Medicni Perspektivi, 2014)
In acute experiments on rabbits there were studied changes in oxygen tension in the intestinal wall tissues, acid-base balance and limited proteolysis and its inhibitors in intestinal venous blood, protective action of L-lysine escinat (0,15 mg/kg / single dose), thiotriazolin (25 mg/kg / single dose), aprotinin (gordox) (10,000 units/kg / single dose) in sequential modeling of standard levels increasing of intra-abdominal hypertension (IAH) — 50, 100, 150, 200, 250, 300, 350 m H2O, and also of tolperison (mydocalm) (5 mg/kg / single dose) on modeling of stable 3-hour IAH 200 m H2O. The IAH modeling was performed by means of stand of our construction. Under the influence of IAH the compensated metabolic acidosis in intestinal venous blood with a compensative hyperpnoe develops, decline of oxygen tension in tissues and activating of a limited proteolysis as well as decline of its inhibitors activity in intestinal venous blood occur. By the degree of metabolic acidosis prevention investigational preparations were distributed as follows gordox > thiotriazolin = L-lysine escinat = mydocalm, and by prevention of decline of oxygen tension in tissues — thiotriazolin > L-lysine escinat > mydocalm > gordox, it is is connected with different rate of methabolic products excretion into the blood, due to the influence on blood circulation and transcapilary exchange. By the degree of prevention of proteolytic activity and inhibitory potential changes, investigational preparations were distributed as follows: gordox > mydocalm > thiotriazolin > L-lysine escinat, this is connected with inhibition of proteolysis in gordox, and in other ones – with reduction of ischemic damage of tissues. Owing to different mechanism of action thiotriazolin, L-lysine escinat and mydocalm may be simultaneously recommended for a conservative treatment of patients with intraabdominal hypertension syndrome.